Volatility Spillover Between Stock Prices and Trading Volume: Evidence From the Pre-, In-, and Post Global Financial Crisis Periods - Ozdemir, Letife (Frontiers in Applied Mathematics and Statistics, 2020)
Stock prices and trading volumes are two important indicators of financial markets. As a result of the fluctuations caused by the economic crises in the markets, it is seen that the variance does not remain constant in financial market data over time. For this reason, in this study, volatility spillover between stock prices and trading volume is examined within the framework of the mixed distributions hypothesis in Turkish capital markets. The causality test in variance was applied to the data covering 02 January 1997- 29 December 2017 period. In order to identify the impact of the 2008 global financial crisis, the data are divided into three sub-periods: the pre-crisis period (02 January 1997 to 29 September 2008), in-crisis period (3 October 2008 to 30 September 2009) and the post-crisis period (1 October 2009 to 29 December 2017). The findings indicate the existence of bidirectional volatility spillovers between stock price and trading volume in the pre- and post-crisis periods. In the crisis period, there is a unidirectional volatility spillover from stock prices to trading volume. This shows that while the volatility of stock price affects the trading volume with lags in the crisis period, the volatility of stock price and trading volume in the non-crisis periods affect each other. The results include important findings for both policymakers and investors and for future work.